2009
DOI: 10.1016/j.jfe.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Models for sample selection bias in contingent valuation: Application to forest biodiversity

Abstract: In this article, we use two formats of contingent valuation (CV) questions to elicit willingness to pay (WTP) for maintaining biodiversity in forests: the dichotomous choice (DC) or referendum format and the open-ended (OE) question. A large population of French households were surveyed nationwide by phone. The sample of respondents was later divided into two subsamples: people who have recreational activities in forests and those who do not. This dichotomy potentially biases WTP as the decision to have recrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
0
15
0
3
Order By: Relevance
“…Hence, the application of a separate probit model would lead to a loss of econometric efficiency. The simultaneous bivariate probit formulation applied in Garcia et al (2007), which resembles more our own analysis below than the one in Garcia et al (2008), shows efficiency gains in the estimation procedure but a relatively small correction of the mean WTP estimate.…”
Section: Respondent Experience and Endogeneity In Contingent Valuatiomentioning
confidence: 83%
See 2 more Smart Citations
“…Hence, the application of a separate probit model would lead to a loss of econometric efficiency. The simultaneous bivariate probit formulation applied in Garcia et al (2007), which resembles more our own analysis below than the one in Garcia et al (2008), shows efficiency gains in the estimation procedure but a relatively small correction of the mean WTP estimate.…”
Section: Respondent Experience and Endogeneity In Contingent Valuatiomentioning
confidence: 83%
“…As in Whitehead (2006), the loss in econometric efficiency was avoided by the simultaneous estimation of two equations: one for the WTP for the curbside recycling program and another one for decision whether or not to reduce the container size, as the authors detected endogeneity behind these two decisions. Garcia et al (2007Garcia et al ( , 2008 in their recent study of WTP for forest biodiversity preservation in France used a similar approach. In particular, these authors argue that the value a respondent places on biodiversity preservation may vary depending on whether the respondent is a forest visitor or not.…”
Section: Respondent Experience and Endogeneity In Contingent Valuatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The contingent valuation method has been the focus of intensive study for several decades, resulting in a number of works describing theory and methods in relation to the valuation of natural resources, environmental amenities and public goods (see e.g. Bateman, Willis 2001;Champ et al 2003;Pearce et al 2006;Mayor et al 2007;Garcia et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies have underlined the significance of an individual's location on the WTP (Garcia et al 2009; Loomis et al 2000; Loureiro and Ojea 2008;Wang et al 2007). Beaumais et al (2008), evaluating preservation of the Seine Estuary wetlands, found significant differences in WTP between inhabitants in the rural countryside and those of large cities (who were ready to contribute more to protect the wetlands).…”
Section: Introductionmentioning
confidence: 99%